Video coaching in practice. Issue 2 (7th February 2014) - Grosdidier, Sheila
Abstract : Video coaching can be a useful tool for identifying strengths and weaknesses in the consulting room. Sheila Grosdidier explains the benefits of this style of training, what to consider when implementing it, and what results to expect.